2008
DOI: 10.3177/jnsv.54.61
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Potential and Antioxidants in the Heart Tissue of .BETA.-Alanine- or Taurine-Treated Old Rats

Abstract: SummaryThe aim of this study was to investigate the effect of the changes of taurine levels in the hearts of old rats on endogenous malondialdehyde (MDA) and diene conjugate (DC) levels and ascorbic acid (AA)-and NADPH-induced lipid peroxidation as well as nonenzymatic (glutathione, vitamin E and vitamin C) and enzymatic antioxidants (superoxide dismutase, glutathione peroxidase and glutathione transferase). Two groups of old (22 mo) rats were treated with ␤ -alanine (3%, w/v; in drinking water), a taurine dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…The treatment caused a 77% decrease in the concentration of taurine in the LV. This decrease in taurine concentration is higher than those observed by Parildar et al [14] and Dawson Jr. et al [15] (20% and 50% respectively). The difference can be explained by the age of the animals used in the experimental protocols.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The treatment caused a 77% decrease in the concentration of taurine in the LV. This decrease in taurine concentration is higher than those observed by Parildar et al [14] and Dawson Jr. et al [15] (20% and 50% respectively). The difference can be explained by the age of the animals used in the experimental protocols.…”
Section: Discussioncontrasting
confidence: 56%
“…The animals were housed in individual cages; their feeding was monitored daily, and water was administered ad libitum . In group T (-), 3% β-alanine (diluted in water), a well known antagonist of taurine transport, was administered [14], [15]. The consumption of water or solution was measured every other day.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we also determined that taurine administration significantly elevated spleen taurine content in both taurine and taurine?endotoxemia groups, a similar finding as previous studies. Parildar et al [47,48] used a rat model to investigate the influence of chronic taurine treatment on prooxidant-antioxidant balance in several tissues. They reported that taurine levels were significantly increased in the brain, heart and liver tissues of taurine-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of taurine having major cellular effects during cardiac insults, this work suggests that LV of diabetics is likely to show similar vulnerability to reperfusion injury compared to non-diabetics. However, the right ventricle of non-diabetics with low taurine could be either preconditioned and more resistant to insults (Allo et al 1997) or more vulnerable due to less available taurine to help efflux accumulated Na + and to oppose oxidative stress and apoptotic death (Chapman et al 1993; Suleiman et al 1992) (Parildar et al 2008; Schaffer et al 2010, 2014; Takahashi et al 2003; Takatani et al 2004a, [b]). Interestingly, taurine deficiency, rather than accumulation, has been implicated in the development of cardiomyopathy (Ito et al 2008) and therefore it can be argued that taurine accumulation is in fact an adaptation to disease development.…”
Section: Discussionmentioning
confidence: 99%